The Aristotelian Tradition in Syriac - Watt, J. W.
1 online resource.
Keywords: This volume presents a panorama of Syriac engagement with Aristotelian philosophy primarily situated in the 6th to the 9th centuries, but also ranging to the 13th. It offers a wide range of articles, opening with surveys on the most important philosophical writers of the period before providing detailed studies of two Syriac prolegomena to Aristotle's Categories and examining the works of Hunayn, the most famous Arabic translator of the 9th century. Watt also examines the relationships between philosophy, rhetoric and political thought in the period, and explores the connection between earlier Syriac tradition and later Arabic philosophy in the thought of the 13th century Syriac polymath Bar Hebraeus. Collected together for the first time, these articles present an engaging and thorough history of Aristotelian philosophy during this period in the Near East, in Syriac and Arabic.